Urgensi Pengaturan Green Economy dalam Undang-Undang Persaingan Usaha Indonesia - Junika Sari , Niken; Nazar, Jasman (Komisi Pengawas Persaingan Usaha, 2025)
The accelerated implementation of Indonesia's green economy is imperative to achieve the Golden Indonesia 2045 vision and the Net Zero Emission target by 2060. However, this initiative is confronted with intricate constraints, including regulatory limitations and ineffective supervisory mechanisms. The Indonesian Competition Law is reputed to possess the capacity to function as an effective instrument in accelerating the implementation of the green economy in Indonesia. Furthermore, there are several crucial aspects that underlie the urgency of regulating the green economy in the Indonesian Competition Law. The objective of this research was to ascertain the role of the Competition Law in accelerating the implementation of the green economy and the urgency of green economy arrangements in the Indonesian Competition Law. Using a normative legal research method with comparative, statutory, and conceptual approaches, the findings indicate that Indonesian Competition Law can play a crucial role. This is achievable through the integration of environmental protection aspects into the framework of the Indonesian Competition Law. Furthermore, the formulation of specific exemption provisions and green guidelines for agreements between business actors focused on environmental protection is expected to have a significant impact on accelerating and optimizing the implementation of the green economy in Indonesia.